Intellectuals in revolution (M. Azuela «The Underdogs», A. Fadeyev «The Rout») - Садовська, Юлія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The present article is devoted to the comparison of the externally distant literature objects – Mexican writer M. Azuela’s novel «The Underdogs» and Russian writer A. Fadeyev’s novel «The Rout». The right for the parallel analysis is provided by the common theme of the intellectuals’ participating in the revolutionary events. The internal contradictions in the perception of the revolutionary ideology and the leveling of the «disguised enemy» personality are investigated. It is proven that loneliness and despair of the intellectuals in revolution is a common literary conflict of the 20s of the XXth century.